Financing constraints and the timing of innovations in the German services sector - Martin Kukuk; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1999)
Using newly available data at the firm level, this study provides convincing evidence of the importance of financial constraints in explaining the timing of innovations in the German services sector. Based on a dynamic model of firms' optimal R&D behavior under financial constraints, we estimate various versions of an econometric specification of the model with dichotomous innovation data by using a univariate ordered probit model. Our results are consistent with the theoretical view that, because of capital markets imperfections, internal finance should be an important determinant of innovative activities by private firms in the manufacturing sector as well as in the services sector.
urn:nbn:de:bsz:21-opus-21314
Keywords: G30; O31; C4; 330; Innovation; Financial Constraints; Ordinal Regressors; Indirect Inference Estimation; Dienstleistungssektor; Innovation; Forschung; Betriebliche Terminplanung; Theorie der Unternehmung; Unternehmensfinanzierung; Theorie; Schätzung; Deutschland